Clinical Sports Medicine - Sedlaček M; Ružić L; Cigrovski V (Deutsche Zeitschrift für Sportmedizin, 2019)
Problem: Lower altitude stay (1250m) and extensive recreational aerobic activity like skiing at lower to moderate altitude (1250-2000m) and its effect on oxygen transport parameters had not been thoroughly investigated.Methods: The experimental group (N=17) underwent an intervention, a typical 10-day ski-trip. They slept at 1250 m and performed 5-6 hours of aerobic activity (skiing) at 1250-2000m altitude. The control group (N=15) stayed at sea level and performed their regular activities. The ferritin levels, reticulocyte count, RBC parameters and erythropoietin before and 48 h after the trip were measured in both groups.Results: The reticulocyte count increased (44.516.6 to 67.919.18 G/L) and somewhat surprisingly erythropoietin decreased in experimental group (6.042.39 to 4.911.54 IU/L, ANOVA p=<0.001). Ferritin levels decreased and reticulocyte count increased in 88% of all experimental group subjects while in control group it changed in both directions. The initial erythrocyte concentration was foundto be a good predictor of reticulocyte increase changes,while ferritin reserveswasdid not. No significant changes after intervention were observed in other parameters.Discussion: In recreational population, sleeping at lower altitudes in combination with aerobic activity of longer daily duration like skiing, elicits changes in erythropoiesis.KEY WORDS: Altitude, Training, Hypoxia, Ferritin, Reticulocyte, Erythropoietin